2008
DOI: 10.1007/s10637-008-9117-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of a peptide combination in gastrointestinal cancers targeting multiple neuropeptide receptors

Abstract: A novel peptide combination consisting of four synthetic neuropeptide analogs of Vasoactive Intestinal Peptide (VIP), Bombesin, Substance P and Somatostatin has been found to have potent anticancer activity in vitro and in vivo. The receptors of these four neuropeptides are known to be over expressed in various cancers. We have found the presence of native neuropeptides in the culture supernatant of the primary tumor cells of human colon adenocarcinomas. It was further demonstrated by receptor-ligand assays th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In our previous study, we first reported that testes-specific protease 50 (TSP50) was abnormally and highly expressed in CRC and represented a potential effective predictor of poor prognosis in CRC patients, making it an attractive novel target for molecular imaging and therapy [30]. Several previous reports demonstrated that the VPAC1 receptor is highly expressed in CRC and plays a major role in the progression of CRC [11], [14], making it one of the most promising novel candidate markers for early CRC detection. Therefore, the screening and identification of peptides that specifically bind to the VPAC1 receptor will aid the development of novel probes for CRC detection and therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we first reported that testes-specific protease 50 (TSP50) was abnormally and highly expressed in CRC and represented a potential effective predictor of poor prognosis in CRC patients, making it an attractive novel target for molecular imaging and therapy [30]. Several previous reports demonstrated that the VPAC1 receptor is highly expressed in CRC and plays a major role in the progression of CRC [11], [14], making it one of the most promising novel candidate markers for early CRC detection. Therefore, the screening and identification of peptides that specifically bind to the VPAC1 receptor will aid the development of novel probes for CRC detection and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the cell surface profile between cancer cells and their normal counterparts can be utilized as a molecular signature for targeted imaging. Furthermore, the overexpressed VPAC1 receptors play a major role in the progression of a number of malignancies, including cancers of the lung, brain, gut, and prostate in addition to neuroblastomas [13], [14], and they mediate tumor angiogenesis through the transactivation of epidermal growth factor receptor (EGFR) and the expression of vascular endothelial growth factor (VEGF) [15], [16]. Thus, these data indicate that the VPAC1 receptor is a potential target for tumor diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they caused partial tumor regression in nude mice xenografts suggesting that they may have use as novel anticancer molecules. DRF 7295 comprises of such novel analogs of the four neuropeptides with in vitro and in vivo efficacy [2]. The inhibition of specific signaling pathways represent a novel approach in cancer drug design.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic study of some of these peptide growth factors modulating the growth and proliferation of primary human adenocarcinoma cells led to the development of DRF 7295. A combination of four peptide analogs -DRF 7295 exhibited potent and selective anti-neoplastic activity in human adenocarcinoma cells in vitro and in vivo, [2]. These analogs include VIP receptor binding inhibitor, LeuMet-Tyr-Pro-Thr-Tyr-Leu-Lys-OH, the bombesin antagonist, D-Phe-Gln-Trp-Ala-Val-Aib-His-Leu-NH 2 ; the substance P antagonist, D-Arg-Pro-Lys-Pro-D-Phe-Gln-D-Trp-Phe-D-Trp-Leu-Ac5c-NH 2 ; and the somatostatin analogue (with a disulphide bond between Cys and Pen amino acids) D-Phe-Cys-Tyr-D-Trp-Orn-Thr-Pen-Thr-NH 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation